The ultrasound-guided percutaneous release technique for De Quervain's disease using an acupotomy - Shen, Yifeng; Zhou, Qiaoyin; Sun, Xiaojie; Qiu, Zuyun; Jia, Yan; Li, Shiliang; Zhang, Weiguang (Frontiers in Surgery, 2023)
Background. This study aimed to compare the effectiveness and safety of the percutaneous first extensor compartment performed by acupotomy procedure with or without ultrasonic (US) guidance. Methods. The percutaneous release was performed with an acupotomy on 40 wrists of cadavers, which was divided into US guidance operation and blind operation. Each arm was dissected and assessed regarding the amount of release and the extent of neurovascular and tendon injury. An analysis of finite biomechanical elements based on wrists specimen data is analyzed to observe the stress of the first extensor tendon compartment. A prospective study observed the pain visual analogue score(VAS) and Patient-Rated Wrist Evaluation (PRWEB) changes after the ultrasound guidance or blind acupotomy treatment in 30 dQD patients. Results. The success rate in the ultrasound-guided technique was 85%, and the blind technique was 70% in the cadaver study, both techniques without neurovascular injury. There was no statistically significant difference between the two groups in measuring the distance from the incision marks to the blood vessels and nerves ( P > 0. 05). According to the biomechanical analysis, the tendon comes out with friction when the wrist is upright. When the wrist is flexed, the tendon and tendon sheath is stressed in the bone ridges. In this prospective study, both ultrasound guidance and blind acupotomy treatment achieved well improvements in pain and function( P<0. 05), but the results with no statistically significant between groups ( P > 0. 05). Conclusion. Both blind and US-guided percutaneous release by acupotomy of the first extensor tendon compartment can get a good result. US-guided techniques can improve the success rate during acupotomy operations, especially for beginners and followers.